2017
DOI: 10.1182/bloodadvances.2017007435
|View full text |Cite
|
Sign up to set email alerts
|

Pak2 regulates myeloid-derived suppressor cell development in mice

Abstract: Key Points Pak2 negatively regulates CD11bhighGr1high MDSC development in mice via both cell-intrinsic and extrinsic mechanisms. Pak2 disruption activates STAT5 while downregulating the expression of IRF8, a well-described myeloid transcription factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…To determine absolute cell numbers in blood, white blood cell counts were determined using a HemaVet 950 (Drew Scientific, Miami Lakes, FL, USA). 40 Plasma and DC stimulation BALB/c mice received BEN or CY on day −2, TBI on day −1, and were sacrificed on day 0. Blood was collected by cardiac puncture for plasma isolation and splenic dendritic cells (DCs) were isolated using a Pan DC Isolation Kit (Miltenyi Biotec; 130-100-875).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…To determine absolute cell numbers in blood, white blood cell counts were determined using a HemaVet 950 (Drew Scientific, Miami Lakes, FL, USA). 40 Plasma and DC stimulation BALB/c mice received BEN or CY on day −2, TBI on day −1, and were sacrificed on day 0. Blood was collected by cardiac puncture for plasma isolation and splenic dendritic cells (DCs) were isolated using a Pan DC Isolation Kit (Miltenyi Biotec; 130-100-875).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Of note, anti-mouse Gr-1 clone RB6-8C5 has been shown to react strongly with Ly6G (a marker for granulocytic MDSCs) and more weakly with Ly6C (a marker for monocytic MDSCs), resulting in a delineated Gr-1 high population, representing the Ly6G + granulocytic MDSCs, and a Gr-1 mid population, representing the Ly6C + monocytic MDSCs [38]. To determine absolute cell numbers in blood, white blood cell counts were determined using a HemaVet 950 (Drew Scientific, Miami Lakes, FL) [39]. Cells were analyzed for reactive oxygen species (ROS) using a Cellular ROS Detection Assay Kit (Abcam, Cambridge, UK).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Cells were frozen in dry pellets before mRNA isolation using the RNeasy Kit (Qiagen, Hilden, Germany). cDNA was generated, and quantitative realtime polymerase chain reaction (qRT-PCR) was performed and analyzed as described previously [39,41].…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…In this knockout model, a significant increase in granulocytes in vivo was observed. Further work ( 66 ) determined that these granulocytic cells were indeed PMN-MDSCs based on their T cell suppressive behavior, and that the overall number and suppressive function of PMN-MDSCs from the conditional Pak2 knockout host was greater than that of the wild-type controls. Importantly, they identified that Pak2-deficiency sensitized myeloid progenitors to GM-CSF stimulation, which led to the accumulation of PMN-MDSCs.…”
Section: Transcriptional Regulators Of Pmn-mdscsmentioning
confidence: 99%